2017
DOI: 10.1111/jocn.13444
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting difficult peripheral intravenous cannulation in adults: a prospective observational study

Abstract: These results can help nurses to recognise risk factors for difficult intravenous access and pay appropriate attention when attempting a venepuncture to preserve patients' peripheral veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 21 publications
5
75
0
16
Order By: Relevance
“…30 Seven studies had "diffi cult" or "diffi culty" in their title as a term to use to describe insertion failure. 3,19,[24][25][26][27]30 One study was titled exclusively for the nursing profession, 20 5 studies were reported in medical journals, 3,24,26,29,30 and 6 were reported in nursing journals, [19][20][21][22]25,27 with the remainder published in a vascular access journal. 23,28 General Characteristics of Included Studies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Seven studies had "diffi cult" or "diffi culty" in their title as a term to use to describe insertion failure. 3,19,[24][25][26][27]30 One study was titled exclusively for the nursing profession, 20 5 studies were reported in medical journals, 3,24,26,29,30 and 6 were reported in nursing journals, [19][20][21][22]25,27 with the remainder published in a vascular access journal. 23,28 General Characteristics of Included Studies…”
Section: Resultsmentioning
confidence: 99%
“…One TRA which was registered as a clinical trial 24 involved a standardized reporting tool as is recommended by the EQUATOR Network. 18 Nine of the 13 papers reported that TRA components were chosen based on identifi ed predictors of successful insertion from observational data 3,19,[23][24][25][26][27][28]30 , with 5 papers using multivariate logistic regression to identify independent predictors. 3,23,24,26,2 At least 4330 insertion attempts on patients were reported.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search found ten studies investigating 21 patient risk factors, including age, gender, race, weight/BMI, medical diseases and conditions (such as diabetes, cancer, lymphadenectomy, previous chemotherapy or radiotherapy, oedema, parenteral drug abuse) (Armenteros‐Yeguas et al, ; Bensghir et al, ; Carr, Rippey, Cooke, et al, ; Fields, Piela, Au, & Ku, ; Jacobson & Winslow, ; Juvin, Blarel, Bruno, & Desmonts, ; Lapostolle et al, ; Van Loon, Puijn, Houterman, & Bouwman, ; Piredda et al, ; Sebbane et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The evidence is summarised in Table . The risk factors for DIVA classified as strong evidence were as follows: gender, BMI, lymphadenopathy, chemotherapy through PIVC or port and hypovolaemia (Armenteros‐Yeguas et al, ; Bensghir et al, ; Fields et al, ; Juvin et al, ; Van Loon et al, ; Piredda et al, ; Sebbane et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation